Phase I/II trial of the CXCR4 inhibitor plerixafor in combination with bortezomib as a chemosensitization strategy in relapsed/refractory multiple myeloma. Issue 11 (4th October 2019) - Ghobrial, Irene M.; Liu, Chia‐Jen; Zavidij, Oksana; Azab, Abdel K.; Baz, Rachid; Laubach, Jacob P.; Mishima, Yuji; Armand, Philippe; Munshi, Nikhil C.; Basile, Frank; Constantine, Michael; Vredenburgh, James; et al.
Abstract: We tested the hypothesis that using CXCR4 inhibition to target the interaction between the tumor cells and the microenvironment leads to sensitization of the tumor cells to apoptosis. Eligibility criteria included multiple myeloma (MM) patients with 1‐5 prior lines of therapy. The purposes of the phase I study were to evaluate the safety and maximal‐tolerated dose (MTD) of the combination. The treatment‐related adverse events and response rate of the combination were assessed in the phase II study. A total of 58 patients were enrolled in the study. The median age of the patients was 63 years (range, 43‐85), and 78% of them received prior bortezomib. In the phase I study, the MTD was plerixafor 0.32 mg/kg, and bortezomib 1.3 mg/m 2 . The overall response rate for the phase II study was 48.5%, and the clinical benefit rate 60.6%. The median disease‐free survival was 12.6 months. The CyTOF analysis demonstrated significant mobilization of plasma cells, CD34+ stem cells, and immune T cells in response to plerixafor. This is an unprecedented study that examines therapeutic targeting of the bone marrow microenvironment and its interaction with the tumor clone to overcome resistance to therapy. Our results indicate that this novel combination is safe and that the objective response rate is high even in patients with relapsed/refractory MM.ClinicalTrials.gov, NCT00903968.